2018
DOI: 10.1039/c8ta08100j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydroxylated group IV metal oxides inside hollow graphitised carbon nanofibers: nano-sponges and nanoreactors for enhanced decontamination of organophosphates

Abstract: The enhanced catalytic properties of hydroxylated group IV metal oxide nanostructures confined within hollow graphitised carbon nanofibers has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Besides that, due to their wide range of pharmacological action, they may be used for the creation of new drugs [205,206] and also as reagents in fine organic synthesis [207][208][209][210][211]. All this makes it relevant to consider the conformational properties of these compounds inside nanotubes, from the perspectives of nanoreactors [68][69][70][71][72][73][74][75] and drug delivery systems [15,19].…”
Section: 3-dioxane In Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, due to their wide range of pharmacological action, they may be used for the creation of new drugs [205,206] and also as reagents in fine organic synthesis [207][208][209][210][211]. All this makes it relevant to consider the conformational properties of these compounds inside nanotubes, from the perspectives of nanoreactors [68][69][70][71][72][73][74][75] and drug delivery systems [15,19].…”
Section: 3-dioxane In Nanotubesmentioning
confidence: 99%
“…On the other hand, the calculated energy barrier for Cl − exchange in the S N 2 reaction within nanotubes was higher by 6.6 kcal/mol in comparison with the gas phase [69]. Later, it was shown that SWCNTs may be used as effective nanoreactors for preparative syntheses of inorganic [70] and organic [71][72][73][74][75] products with high yields; it is also possible to achieve enantiomeric excess of the products by using a racemic mixture of P and M enantiomers of (n,m) chiral nanotubes [76].…”
Section: Introductionmentioning
confidence: 99%
“…[34] Molybdenum dioxide bisacetylacetonate (MoO 2 (acac) 2 ) was thus identified as an ideal precursor and adopted for the gas-phase thermal deposition reaction. [34] Molybdenum dioxide bisacetylacetonate (MoO 2 (acac) 2 ) was thus identified as an ideal precursor and adopted for the gas-phase thermal deposition reaction.…”
Section: Synthesis and Characterization Of Molybdenum Dioxide Nanoparmentioning
confidence: 99%
“…In this study, we utilised graphitised carbon nanofibres (GNF) that have many of the attractive properties of carbon nanotubes, but with the added benefits of (i) large internal diameters (typically larger than 60 nm) enabling the efficient mass transport of reactants and products to and from the internal cavity and (ii) corrugated internal surfaces resulting in the effective stabilisation of nanoparticles, as demonstrated in our previous studies (Figure 1). [33][34][35][36] Herein, successfully prepared ceria nanoparticles within GNF (CeO2@GNF) were analysed by a variety of structural and chemical characterisation techniques, and applied in the preparative-scale reaction of cyclohexene oxidation, revealing key features of nanoscale confinement in carbon nanoreactors important for sustainable organic synthesis. The internal diameters are much larger than the dimensions of simple molecular species (typically by more than an order of magnitude) and the termini are always open, thus facilitating highly efficient transport of molecules through the internal volume.…”
Section: Introductionmentioning
confidence: 99%